The Role of Clinical Hypnotherapy on Quality of Life and Its Relationship with Heart Rate Variability and Serum Endorphin Levels in Solid Cancer Patients - I.A. Browijoyo, H. Shatri, S.D. Elvira, I. Rinaldi, M. Faqieh (South Eastern European Journal of Public Health, 2024)
Introduction:A solid cancer has a noticeable effect on both the physical and psychological health of patients, considerably reducing the quality of life. This then resulted in a decrease in heart rate variability (HRV) and lower serum endorphin levels. The physical symptoms of the disease itself, the adverse effects of treatment, and the psychological distress associated with the diagnosis and treatment process can all contribute to the development of profound emotional and social challenges. Objectives: This review explore the efficacy of clinical hypnotherapy as a holistic psychological intervention by examining its effect on quality of life, HRV, and endorphin levels in solid cancer patients. Methods: A comprehensive review of the literature was undertaken with the aim of evaluating the psychosocial and physiological effects of clinical hypnotherapy on solid cancer patients. The factors investigated included quality of life metrics, HRV as an indicator of autonomic function, and serum endorphin levels. Results: Clinical hypnotherapy has been shown to offer significant benefits for solid cancer patients. It promotes relaxation, reducing stress, and potentially modulating biological markers associated with health, leading to better stress management and enhanced quality of life. Hypnotherapy interventions have a positive effect on HRV by modulating the autonomic balance and reducing sympathetic overactivity. In addition, empowering patients to take an active role in their pain management, which increases their sense of control and leads to greater emotional well-being, can help to increase endorphin levels and alleviate mood disturbances often seen in these patients. Conclusions: Clinical hypnotherapy has emerged as a promising adjunctive treatment to improve quality life including various physiological and psychological outcomes in solid cancer patients by reducing pain and anxiety, enhancing physical functioning, increasing HRV, and potentially influencing endorphin levels.